Multicritical Nishimori point in the phase diagram of the ±J ising model on a square lattice - Hasenbusch, Martin; Toldin, Francesco Parisen; Pelissetto, Andrea; Vicari, Ettore (Physical review. E, Statistical, nonlinear, and soft matter physics, 2008)
We investigate the critical behavior of the random-bond ±J Ising model on a square lattice at the multicritical Nishimori point in the T−p phase diagram, where T is the temperature and p is the disorder parameter (p=1 corresponds to the pure Ising model). We perform a finite-size scaling analysis of high-statistics Monte Carlo simulations along the Nishimori line defined by 2p−1=tanh(1/T), along which the multicritical point lies. The multicritical Nishimori point is located at p∗=0.890 81(7), T∗=0.9528(4), and the renormalization-group dimensions of the operators that control the multicritical behavior are y1=0.655(15) and y2=0.250(2); they correspond to the thermal exponent ν≡1/y2=4.00(3) and to the crossover exponent ϕ≡y1/y2=2.62(6).